2012
DOI: 10.1007/s10661-012-2569-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transgenic Bt cotton on soil fertility and biology under field conditions in subtropical inceptisol

Abstract: Although there is large-scale adoption of Bt cotton by the farmers because of immediate financial gain, there is concern that Bt crops release Bt toxins into the soil environment which reduces soil chemical and biological activities. However, the majorities of such studies were mainly performed under pot experiments, relatively little research has examined the direct and indirect effects of associated cover crop of peanut with fertilization by combined application of organic and inorganic sources of nitrogen u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 41 publications
4
17
0
Order By: Relevance
“…4). Similar results were observed in other short-term studies 21, 30 or long-term studies on Bt maize 36, 56 . The fact that microbial metabolic quotients among Bt rice treatments were close to one another also suggested that soil microbial biomass was not affected by Bt rice Kefeng-6 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…4). Similar results were observed in other short-term studies 21, 30 or long-term studies on Bt maize 36, 56 . The fact that microbial metabolic quotients among Bt rice treatments were close to one another also suggested that soil microbial biomass was not affected by Bt rice Kefeng-6 .…”
Section: Discussionsupporting
confidence: 91%
“…In addition, soil respiration could be significantly increased 27, 28 or decreased 25 by transgenic Bt maize in different studies. Most of these reported studies were based on short-term field experiments, up to two or three years 13, 29, 30 , enabling us to learn what and how Bt crops affect soil microbial organisms and soil eco-processes. However, short-term cultivation experiments encountered temporal variations in soil environment and crop growth, were not able to reflect the accumulative effects of Bt protein along with the food web in the soil, it is still poorly understood whether long-term cultivation of Bt crops will result in irreversible impacts on soil health.…”
Section: Introductionmentioning
confidence: 99%
“…Soil DHA reflects the total range of oxidative activity of soil microflora and, consequently it may be a good indicator of microbiological activity in the soil (Skujins 1976). Positive correlations between dehydrogenase activity and Bt cotton cultivation are also reported (Singh et al 2013). DHA in soil depends on the content of soluble organic carbon (Zaman et al 2002) and the increased organic matter in the surface soil horizon enhanced the soil enzyme activities.…”
Section: Resultsmentioning
confidence: 91%
“…Numerous studies have been carried out to investigate the effects of transgenic crops on soil microbial communities [1][2][3]. Most results indicate that transgenic Bt crops have not caused significant effects on soil microbes compared to conventional crops [4][5][6][7][8][9][10]. OsrHSA transgenic rice is transformed with the human serum albumin gene that produces a soluble medicinal globular protein [11] that has attracted attention regarding its environmental safety.…”
Section: Introductionmentioning
confidence: 99%